PENGARUH PERILAKU KEWIRAUSAHAAN DAN STRATEGI PEMASARAN TERHADAP KEBERHASILAN USAHA PENGUSAHA REKLAME DI JALAN PANGERAN HIDAYAT PEKANBARU - Sibuea, Harkemri Sibuea Harkemri; Syabrus, Hardisem Syabrus Hardisem; ', Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to find out the influence of entrepreneurial behavior and marketing strategy to success of reklame business in Pangeran Hidayat street Pekanbaru. The research was carried out in July-August 2015. Object of this research are 30 reklame business owners. This type of research is descriptive quantitative. Data analysis technique used is the multiple regression analysis and using questionnaire to collect the data. The result obtained in the research stated that, simultaneously and partially, the entrepreneurial behavior and marketing strategy influences has a positive and significant factor to the succeed a business. And the magnitude of the effect of entrepreneurial behavior and marketing strategy to success of reklame business in the way of a pangeran hidayat street Pekanbaru is equl to 62,4%, while the rest in influenced by other factors not examined this study, such as capital, row materias, skill, management ability and environmental competition. Form the result, it can be concluded that reklame entrepreneurs in Pangeran Hidayat street Pekanbaru should optimize entrepreneurship behavior and marketing strategy to increase the success of their businesses. It is due to the fact that entrepreneur behavior and marketing strategy has a positive and significant influence towards the success of business.Key Words: Entrepreneurship Behaviour, Marketing Strategy, Successful Business, Profit